2022
DOI: 10.1055/a-1766-6790
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A in Serum and Plasma Rich in Growth Factors (PRGF) Eye Drops

Abstract: Background Vascular endothelial growth factor (VEGF)-A, the most abundant subtype of the VEGF family in the eye, plays an important role in corneal homeostasis due to its ability to mediate corneal nerve repair. Repeated intravitreal anti-VEGF injections were shown to significantly reduce corneal nerve density, which might negatively affect corneal homeostasis and lead to a neuropathic dry eye disease. Currently, there are two effective modalities to treat dry eye while supplying VEGF to the ocular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…There are many widely varying VEGF values reported in the literature, e.g., for patients with DES: 68.76 ± 38.70 pg/mL; for control group: 65.57 ± 34.45 pg/mL -slight difference between patients with and without DES [21]. On the other hand, Sanak et al reported mean values of 238.7 ± 146.6 pg/mL for serum -more than 3 fold higher than for plasma rich in growth factors (PRGF) [22]. Yet, apart from cytokines and VEGF, there are many more proteins in serum that have positive effect the eye.…”
Section: Discussionmentioning
confidence: 97%
“…There are many widely varying VEGF values reported in the literature, e.g., for patients with DES: 68.76 ± 38.70 pg/mL; for control group: 65.57 ± 34.45 pg/mL -slight difference between patients with and without DES [21]. On the other hand, Sanak et al reported mean values of 238.7 ± 146.6 pg/mL for serum -more than 3 fold higher than for plasma rich in growth factors (PRGF) [22]. Yet, apart from cytokines and VEGF, there are many more proteins in serum that have positive effect the eye.…”
Section: Discussionmentioning
confidence: 97%